2020
DOI: 10.1093/jac/dkaa347
|View full text |Cite
|
Sign up to set email alerts
|

Dimercaptosuccinic acid in combination with carbapenems against isogenic strains of Escherichia coli producing or not producing a metallo-β-lactamase in vitro and in murine peritonitis

Abstract: Background Carbapenemase-producing Enterobacterales represent a major therapeutic challenge. MBLs, requiring zinc at their catalytic site, could be inhibited by meso-dimercaptosuccinic acid (DMSA), a heavy metal chelator already widely used for treating lead intoxication. Objectives To evaluate the activity of carbapenems alone or combined with DMSA against MBL-producing Escherichia coli in a severe murine peritonitis model. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…97 One in vivo study showed that a zinc chelator (DMSA) used in combination with a carbapenem significantly reduced bacterial counts in an MBL-producing E. coli murine peritonitis model compared to carbapenems alone. 98 The clinical implications of these findings remain uncertain. While some case reports have shown mostly positive outcomes with carbapenem-based regimens for infections caused by MBL-producing Enterobacterales, 99 Falcone et al noted that among 6 patients who received meropenemcontaining combinations, 3 of them died, though none of them were receiving carbapenem monotherapy.…”
Section: Carbapenemsmentioning
confidence: 99%
“…97 One in vivo study showed that a zinc chelator (DMSA) used in combination with a carbapenem significantly reduced bacterial counts in an MBL-producing E. coli murine peritonitis model compared to carbapenems alone. 98 The clinical implications of these findings remain uncertain. While some case reports have shown mostly positive outcomes with carbapenem-based regimens for infections caused by MBL-producing Enterobacterales, 99 Falcone et al noted that among 6 patients who received meropenemcontaining combinations, 3 of them died, though none of them were receiving carbapenem monotherapy.…”
Section: Carbapenemsmentioning
confidence: 99%
“…We used the lethal murine intraperitoneal infection model previously developed by our group [13,[15][16][17]. Mice were inoculated by the intraperitoneal route with 250 µL of a bacterial suspension in porcine mucin 10% (Sigma-Aldrich), corresponding to a final inoculum of approximately 2.5 × 10 7 CFU/mL.…”
Section: Murine Peritoneal Infection Modelmentioning
confidence: 99%
“…We developed a high-inoculum severe murine peritonitis model, responsible for 100% mice mortality in the absence of treatment. This model allows testing for animal survival and bacterial counts in the spleen and organ sterilization and is especially interesting to test for the efficacy of combinations of antibacterials [13,[15][16][17].…”
Section: Introductionmentioning
confidence: 99%